Proses Belajar dan Prestasi Akademik: Tinjauan atas Keyakinan Diri, Minat Baca, Model Pembelajaran, Penggunaan Media, dan Dukungan Sosial - Didit Darmawan; Muhammad Alifkhan (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2026)
This literature study aims to analyze the interaction between self-efficacy, reading interest, learning models, media utilization, and social support in shaping the learning process and academic achievement of students. The method used is qualitative library research with a thematic synthesis approach following systematic literature review procedures. The results indicate that self-efficacy provides motivational drive and psychological resilience enabling students to face academic challenges with optimism and persistence. Reading interest provides access to various knowledge sources and trains cognitive abilities necessary for deep understanding. Appropriate learning models create structures and experiences that facilitate active knowledge construction. Effective media utilization enriches learning experiences and makes abstract concepts more concrete and comprehensible. Social support from parents, teachers, and peers provides emotional and instrumental foundations enabling students to persist and thrive in the learning process. These five factors mutually reinforce each other and collectively form an educational ecosystem that determines the quality of the learning process and the level of academic achievement. This study contributes theoretically to enriching the ecological perspective on educational psychology and practically provides reflective foundations for teachers, parents, and schools in optimizing the interplay of affective, cognitive, and social factors that shape student success.